2002
DOI: 10.1097/00005373-200212000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Release of Abdominal Compartment Syndrome Improves Survival in Patients with Burn Injury

Abstract: Abdominal release for patients with ACS and severe burn injury results in physiologic improvement and a 40% survival rate. We recommend bladder pressure monitoring for all patients with severe burn injuries and abdominal decompression in any patient who develops pressures greater than 30 mm Hg if they have signs of physiologic compromise. Aggressive expectant management can effect a 40% survival rate in this group of severely injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(61 citation statements)
references
References 13 publications
2
52
0
4
Order By: Relevance
“…[12][13][14][15] A resuscitation volume greater than 237 ml/kg over the course of 12 hours (or 16 liters during a 12-hour period in a 70-kg man) appears to be the threshold for the development of ACS. 16 ACS results in decreased renal blood flow and subsequent renal failure, intestinal ischemia, respiratory failure, and death if not recognized even and treated early. 17 The treatment of ACS by drain placement and abdominal escharotomy followed by the last resort of a decompressive laparotomy may improve survival but is associated with dramatic increases in morbidity.…”
Section: Consequences Of Over-resuscitationmentioning
confidence: 99%
“…[12][13][14][15] A resuscitation volume greater than 237 ml/kg over the course of 12 hours (or 16 liters during a 12-hour period in a 70-kg man) appears to be the threshold for the development of ACS. 16 ACS results in decreased renal blood flow and subsequent renal failure, intestinal ischemia, respiratory failure, and death if not recognized even and treated early. 17 The treatment of ACS by drain placement and abdominal escharotomy followed by the last resort of a decompressive laparotomy may improve survival but is associated with dramatic increases in morbidity.…”
Section: Consequences Of Over-resuscitationmentioning
confidence: 99%
“…Studies in children are limited, but it has been shown that early abdominal decompression results in rapid return of vital parameters to pre-ACS levels in both children and adults (2,7). Decompressive management is traditionally performed via laparotomy; however, some cases may improve with percutaneous drainage of abdominal fluid (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Resolution of the ACS can significantly improve outcome in patients without primary abdominal disease that develop multiple organ dysfunction. 16,17 The effects of elevated IAP on organ function are well documented. [18][19][20][21] Visceral perfusion, abdominal blood flow, central venous pressure (CVP), pulmonary pressures, cardiac output, and renal function are all adversely affected by an increasing IAP, and early changes can be seen when levels exceed 10 cm H 2 O.…”
Section: Pathophysiologymentioning
confidence: 99%